Effectiveness of TRIZ Invention for Enhancing Design Creativity in High School Students: The role played by teacher self-efficacy - Dongna, Liu; Sharul, Azim Bin Sharudin@Sharaddin (South Asian Journal of Social Sciences and Humanities, 2025)
As education systems evolve to prepare learners for the challenges of the 21st century, there is  an earnest need for a holistic educational approach that embraces creativity, innovation, and  empowers both teachers and students to offer new insights and creative ideas to survive in the  future era. For this purpose, there are different pedagogical interventions such as TRIZ can  bring many incumbent benefits and prosperities in the educational context. However, China  has a slow pace towards this beneficial strategy and the major reason behind this factor is their  conventional conceptions and resistance of teachers and others to embrace new technology.  Therefore, this study has proposed a conceptual framework where the study has illuminated  previous literature associated with TRIZ, design creativity, teachers’ efficacy and the  challenges associated with TRIZ. The study followed a review strategy and explored the last 5  years' papers to gather relevant empirical information from the research. In conclusion, the  study has shared that TRIZ is a radical systematic approach that is a great opportunity for  educators and policymakers to transform the Chinese educational system and equip educators  and students with design creativity and problem-solving skills. However, this beneficial  intervention strategy is confined to different conventional challenges and issues as resistance  to innovation.
Keywords: TRIZ methodology; Design creativity; Teacher self-efficacy; Creative problem solving; China